Ability of dental students in detection of proximal caries - Tavakoli, Ehsan; Davari, Abdolrahim; Javadi, Zoleikha Sadaat; Ghaffari Targhi, Mehrdad (Journal of Dental School, 2019)
Objective: Tooth decay is one of the most common chronic diseases in the world. After pit and fissures, enamel of proximal surface is the second region prone to rot. Bitewing images are one of the most important diagnostic tools for the detection of caries. Given the importance of accurate and timely detection of decay, the current study was aimed to evaluate the ability and skill of the final- year dental students to identify the presence and depth of proximal caries in dental bitewing radiography. Methods: In this descriptive cross-sectional study 208 inter proximal surfaces among the 13 dental bitewing radiographs were selected randomly. The radiographs were evaluated by two experienced dental specialists (a radiologist and a restorative specialist) to detect inter proximal decay between teeth. These diagnoses were considered as the gold standard. The radiographs were further assessed by fourteen final-year dental students. Finally, the collected data were analyzed by SPSS-17 software using Kappa coefficient of agreement and ICC. The sensitivity and specificity values were also determined. Results: The value of Kappa correlation coefficient to assess the similarity between students’ responses and gold standards was obtained as 0.28 (p<0.001). The Kappa correlation coefficient for evaluation of the precision of the data was 0.71. The sensitivity in the whole population was 0.43, while the specificity was 0.84. Conclusion: According to the results obtained in this study, the performance of final year dental students to identify the presence and depth of proximal caries from bitewing radiographs was not satisfactory. Moreover, the ability to detect normal surfaces was unacceptable.